1995
DOI: 10.1001/archpsyc.1995.03950160046009
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal Symptoms and Signs in the Roscommon Family Study

Abstract: "Schizotypy" is a complex, multidimensional clinical construct, whose various dimensions differ widely both in the degree and specificity with which they reflect the familial liability to schizophrenia. Subpsychotic thought disorder; negative schizotypal signs, such as poor rapport and odd behavior; deficient occupational functioning; and social isolation/avoidance best characterized relatives of schizophrenic probands compared with relatives of matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(61 citation statements)
references
References 32 publications
2
58
1
Order By: Relevance
“…Factor-analytic research has shown that schizotypy and SPD are multidimensional syndromes. It also has been shown that family members of patients with schizophrenia differ from nonrelatives based on the type and severity of schizotypal features, especially odd speech and social dysfunction [32]. Findings such as these have led some to believe that there may be different schizotypal disorders [26,30].…”
Section: Schizotypy Schizotaxia and Schizotypal Personality Disordermentioning
confidence: 99%
“…Factor-analytic research has shown that schizotypy and SPD are multidimensional syndromes. It also has been shown that family members of patients with schizophrenia differ from nonrelatives based on the type and severity of schizotypal features, especially odd speech and social dysfunction [32]. Findings such as these have led some to believe that there may be different schizotypal disorders [26,30].…”
Section: Schizotypy Schizotaxia and Schizotypal Personality Disordermentioning
confidence: 99%
“…Accumulating evidence from family and twin data indicates that SPD is multidimensional and may be genetically heterogeneous. [89][90][91][92] Its manifestations fall into two genetically independent clusters: a 'negative' cluster (odd speech and behaviour, inappropriate affect and social withdrawal), more common among relatives of schizophrenic probands, and a 'positive' cluster (magical ideation, brief quasipsychotic episodes), associated with increased incidence of affective disorders in relatives. 93 'Negative' schizotypy may indeed represent a personality-based counterpart of schizophrenia, 94 manifesting attenuated cognitive deficits [95][96][97] and brain structural abnormalities 98 characteristic of schizophrenia.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…Indeed, nearly all correlations between scores for negative and positive symptoms, calculated for each year in the period of 15 years prior to hospital admission, for each month in the final pre-admission year, and for several time-points in a period up to 3 years after admission, were reported by Häfner et al (1995) to depart significantly and positively from zero, with values varying between 0.15 and 0.45 approximately. Although interpret these correlations and the almost parallel course in terms of a common etiological factor, attention must be drawn to the fact that among biological relatives of schizophrenics predominantly negative symptoms have been reported (see, e.g., Grove et al, 1991;Gunderson, Siever, & Spaulding, 1983;Kendler, McQuire, Gruenberg, & Walsh, 1995;Tsuang et al, 1991). This suggests that negative symptoms, rather than positive ones (and notwithstanding their statistical interdependence), are a more direct expression of the biologicalgenetic basis of schizophrenia.…”
Section: Relationship Between Positive and Negative Symptomsmentioning
confidence: 99%